Biosimilar Drug Development and Safety: Issues with Autoimmune Rheumatic Diseases (ARDs) - Bandyopadhyay, Alok Kumar (British Journal of Healthcare and Medical Research, 2024)
Biosimilar drugs including monoclonal antibodies (mAb) and cytokines, have become mainstream treatments in a few clinical settings starting from pain control, cardiovascular, oncology, and rheumatic arthritis (RA). Autoimmune rheumatic diseases share some observations like immune deregulation, and the presence of inflammatory mediators, can be treated with some effective Biologic disease-modifying antirheumatic drugs. In contrast, the structure and conformation of these medicine during infusion to the body yield anti drug antibody (ADA). Assessment of immunogenicity is an important component of drug safety evaluation. Risk based approach considers both probability of induction of immune response and expected clinical consequences. Tumor Necrosis Factor inhibitors (TNFi) are widely used in this aspect. Immunogenicity response on these treatments is crucial since the appearance of ADAs has consequences in terms of safety and efficacy. The risk of an immune response to a therapeutic protein may dictate treatment-related factors, including concomitant therapies, which may either decrease or increase. Patients with activated immune systems (for example, autoimmune rheumatic diseases orARDs) may be more used to immune responses to therapeutic proteins. Combination with immunosuppressive agents (e.g., methotrexate, MTX) during biologic therapy reduces the risk of ADAs production and may induce tolerance to biologic therapy in patients with ARDs. The frequency of ADAs formation also depends on the disease. For RA, the frequency of ADAs-IFX (infliximab) varies from 0–83% depending on the disease. Treatment of ARDs patients with a few biological agents and status of clinical immunogenicity are discussed.